Pengaruh pemberian pakan pellet dengan level yang berbeda terhadap pertambahan bobot badan harian dan konversi ransum domba - Jeni Rambu Hana; I Made Adi Sudarma (Fakultas Pertanian Universitas Majalengka, 2025)
This study aimed to evaluate the effect of feed treatments on Average Daily Gain (ADG) and feed conversion in rams. The sheep we used were 16 Fat Tail Sheep (FTS) with four treatments and four replications applied: P0 (ad libitum field grass hay as control); P1 (P0 + pellets 0.5% of body weight); P2 (P0 + pellets 1% of body weight); and P3 (P0 + pellets 1.5% of body weight). The parameters observed were average daily gain and feed conversion, and the data were analyzed by ANOVA and further tested using Duncan Multiple Range Test (DMRT) at a 95% confidence level. The results showed that a significant difference (p<0.05) in average daily gain, with the best treatment in P3 at 52.81 g/head/day. Feed conversion also showed a significant difference (p<0.05) between the best treatments in P3, with the best treatment at 15.74. It can be concluded that the addition of pellets with a dose of 0.5% to 1.5% of body weight can increase average daily gain and feed conversion. Therefore, the use of local pellet feed has strong potential as an alternative fattening ration to optimise sheep production performance.